Neonatal Perforated Appendicitis Masquerading as Necrotizing Enterocolitis - Andrew Tumen; Pranit N Chotai; John Matthew Williams; Adrianne Myers-Webb; Jie Zhang; Ramesh Krishnan; James W Eubanks III (EL-Med-Pub, 2017)
A preterm neonate underwent emergent laparotomy for presumed necrotizing enterocolitis (NEC). Intra-operatively, neonatal perforated appendicitis (NPA) was encountered. This may represent a form of NEC localized to the appendix. A high index of clinical suspicion and early laparotomy are recommended.